2020
DOI: 10.1242/jcs.233775
|View full text |Cite
|
Sign up to set email alerts
|

A function of profilin in force generation during malaria parasite motility independent of actin binding

Abstract: During transmission of malaria-causing parasites from mosquito to mammal, Plasmodium sporozoites migrate at high speed within the skin to access the bloodstream and infect the liver. This unusual gliding motility is based on retrograde flow of membrane proteins and highly dynamic actin filaments that provide short tracks for a myosin motor. Using laser tweezers and parasite mutants, we previously suggested that actin filaments form macromolecular complexes with plasma-membrane spanning adhesins to generate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…In divergence from classical profilins, apicomplexan profilins contain an additional β-hairpin loop, which is critically required for actin monomer binding, and a single point mutation in this loop region eliminates a hydrogen-bond, thereby abrogating fast motility seen in P. berghei sporozoites (Moreau et al, 2017). Recently, the same group produced mutations in another acidic loop in profilin, which did not affect actin polymerisation in vitro and yet affected gliding motility of P. berghei sporozoites, indicating that additional factors beyond actin polymerisation are at play during motility and invasion of apicomplexan parasites (Moreau et al, 2020). TgProfilin is critical for the completion of the lytic life cycle as depletion of TgProfilin rendered parasites defective in gliding motility, invasion and host cell egress (Plattner et al, 2008).…”
Section: F-actin Regulation: the Role Of Abps In Maintaining The Actin Networkmentioning
confidence: 99%
“…In divergence from classical profilins, apicomplexan profilins contain an additional β-hairpin loop, which is critically required for actin monomer binding, and a single point mutation in this loop region eliminates a hydrogen-bond, thereby abrogating fast motility seen in P. berghei sporozoites (Moreau et al, 2017). Recently, the same group produced mutations in another acidic loop in profilin, which did not affect actin polymerisation in vitro and yet affected gliding motility of P. berghei sporozoites, indicating that additional factors beyond actin polymerisation are at play during motility and invasion of apicomplexan parasites (Moreau et al, 2020). TgProfilin is critical for the completion of the lytic life cycle as depletion of TgProfilin rendered parasites defective in gliding motility, invasion and host cell egress (Plattner et al, 2008).…”
Section: F-actin Regulation: the Role Of Abps In Maintaining The Actin Networkmentioning
confidence: 99%
“…After calibration, we repeatedly observed that around 70% of wt sporozoites were able to pull a bead out of the trap at 30 pN of force. This percentage was observed at a force of 70 pN in the previous setup (Quadt et al, 2016;Moreau et al, 2017Moreau et al, , 2020. Currently we do not know the source of this difference and as the previous setup was dismantled, we unfortunately cannot compare them sideby-side.…”
Section: Changing Myoa Kinetics Affects Sporozoite Force Productionmentioning
confidence: 80%
“…Parasite motility results from a complex interplay between adhesion and force generation. Yet, force generation of sporozoites has so far only been investigated in parasites lacking either surface receptors or actin-binding proteins without a direct function in force generation (Münter et al, 2009;Hegge et al, 2012;Quadt et al, 2016;Moreau et al, 2017Moreau et al, , 2020. Intriguingly, force generation of sporozoites was found to be lower in mutant parasites that show similar migratory capacity or speeds as wt.…”
Section: Changing Myoa Kinetics Affects Sporozoite Force Productionmentioning
confidence: 99%
“…Profilins are characterized by having three major biochemical functions (Krishnan & Moens, 2009;Moreau et al, 2017Moreau et al, , 2020; firstly, profilins bind to and sequester actin monomers, therefore affecting how actin filaments polymerize. Secondly, profilins have an affinity for proline-rich domains contained within their interacting ligands and lastly, they have an affinity for phosphatidylinositol lipids that dissociate the actin:profilin complexes.…”
Section: Biochemical Characterization Of Fhprofilinmentioning
confidence: 99%